IMPLEMENTASI MOTION GRAPHIC PADA ANIMASI 'AKSI 3M PLUS' MENGENAI PENCEGAHAN PERKEMBANGBIAKAN NYAMUK AEDES AEGYPTI : IMPLEMENTATION OF MOTION GRAPHICS IN THE ANIMATION "AKSI 3M PLUS" ON THE PREVENTION OF AEDES AEGYPTI MOSQUITO BREEDING - Viqki Nur Fajar; Rujianto Eko Saputro (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
Dengue Hemorrhagic Fever (DHF) remains a significant public health issue caused by the transmission of the dengue virus through Aedes aegypti mosquitoes. One of the most effective prevention efforts is the implementation of the 3M Plus movement; however, information dissemination is still largely conducted through conventional media, which are often less engaging and interactive. This study aims to implement motion graphics in the animation entitled “Aksi 3M Plus” as an educational medium for preventing the breeding of Aedes aegypti mosquitoes. The research employed the ADDIE development model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The analysis stage involved identifying media requirements through interviews with the Banyumas Health and Family Planning Office. The design stage produced storyboards and visual asset concepts. During the development stage, vector-based visual assets were created and colored. Motion graphics were implemented using the CapCut application by applying keyframe animation techniques to create dynamic visual movements. The evaluation stage was conducted using the Alpha Testing method involving a subject matter expert and an animation expert. The evaluation results achieved an average score of 92.06%, categorized as excellent. Therefore, the “Aksi 3M Plus” motion graphic animation is considered suitable as an educational medium for DHF prevention.